A MECHANISM AND DETERMINANTS OF AN AGENCY-COST EXPLANATION FOR DIVIDEND PAYMENTS - Hartono, Jogiyanto; Ratnaningsih, Dewi (Gadjah Mada International Journal of Business, 2003)
This study explains the dividend puzzle using the agency-cost frame work suggested by Easterbrook (1984). Easterbrook hypothesized that shareholders in firms, who increase cash dividend payout and âsimultaneously raise debts to finance their investments are likely to be wealthier than those in firms who only increase their cash dividend payout. He provided the mechanism that shareholders use the dividend payments to force managers to go to the capital markets to raise funds. Therefore, he argued that dividend policy influences the financing policy. A system of simultaneous equation using three-stage generalized least square method is used to test the hypotheses. Among the variables to proxy the investment opportunity set, market-to-book ratio, market-to-book assets ratio and accounting earnings-per-share-to-price ratio are the best proxies. Attempt is made to obtain better proxies for the investment opportunity set using an instrument variable method. The system is robust to alternate investment opportunity variables as well as to the instrumental variables. The findings are as follows. For the firms that increase cash dividend payout and raise debt simultaneously, (a) dividend policy is not a shareholders mechanism, but a managers accounting-based decision with accounting earnings and retained earnings as the major determinants, (b) dividend policy influences financing policy, but not the other way around, (c) increasing dividend payment decreases shareholders wealth, but increasing debt subsequently increases shareholders wealth with a net effect positive to shareholders wealth, and (d) dividend policy is independent from investment policy.